Influence Of Liquidity Ratios, Solvency And Profitability Against Share Prices - Roudlotul Firdausyi; Mohammad Syafik (Sean Institute, 2024)
The aim of this research is to determine empirical evidence of the influence of liquidity, solvency and profitability on share prices in mining sector companies. This research is a type of quantitative research. The population in this research is mining sector companies during 2019-2022. The sampling method in this research used a purposive sampling method, with a total of 79 observations. The research method used is panel data regression analysis techniques and uses the STATA (Statistics and Data) application tool. The test results prove that the liquidity ratio proxied by the current ratio (CR) and solvency proxied by the debt to equity ratio (DER) have no effect and are not significant on stock prices, the profitability ratio proxied by return on equity (ROE) has an effect and is significant on stock prices.